Rambutan (Nephelium lappaceum L.) seed oil: extraction and application in food - Dong, Nguyen Kim; Trần, Trần Thị Ngọc Bích; Lam, Lâm Thị Kim Ngân (Hue University Journal of Science: Natural Science, 2025)
The extraction of oil from rambutan seeds and applying oil to food was carried out at a laboratory scale to provide data and factual information about a new type of oil. This paper investigated the influence of the extraction methods (stirring, soxhlet, and ultrasonic), extraction solvent (ethanol and n-hexane), and extraction time (3, 5, 7, and 9 hours) on the extraction efficiency. The oil was applied to produce potato chips. The results show that the highest oil recovery efficiency was 37.7% when using the soxhlet method, n-hexane, and an extraction time of 9 hours. The frying oil temperature affected the colour (L, a, b, ∆E) of the potato chips. When the temperature increased, the values of L and ∆E decreased, whereas the values of a and b increased. In addition, the frying oil temperature has an influence on the smell, taste, and texture of the product. The optimal frying temperature for processing potato chips with good quality was 160 °C. The results of this study show that using by-products from rambutan to create a new kind of oil can satisfy consumers’ needs and diversify the products in the market.